Color and racial attitudes in white, black and biracial children - Félix Neto (1998)
Previous studies of children in United States, Western Europe and Asia have demonstrated a bias favoring the color white relative to the color black, and a bias favoring light-skinned figures relative to dark-skinned figures. In this study of eight-year old children, procedures used in previous studies were administered to biracial children of mixed black and white parentage and to black and white children of monoracial parentage. Both types of bias were found among the three racial categories, providing additional evidence that the pro-white and pro-light-skinned biases are pancultural tendencies. The biases were not different by gender, but they were significantly different by race. Mean color attitudes of white children were significantly different from biracial children, such that the white children displayed a stronger pro-white/anti-black bias than the biracial children. Mean racial attitudes of white children were significantly different from black and biracial children, with white children showing more pro light-skinned bias than black and biracial children. It appears that the biracial category should be considered in research on color and racial attitudes.